Attachment orientations and reactivity to humor in a social support context. (February 2014) - Howland, Maryhope; Simpson, Jeffry A.
In this behavioral observation study, we tested how individuals' use of affiliative and aggressive humor (observer rated) impacted their romantic partners' mood in a social support context. We also examined whether the attachment orientations of the humor-receiving partners moderated the humor effects. As predicted, support providers' use of affiliative humor predicted pre- to post-discussion decreases in support recipients' negative mood. Providers' use of aggressive humor predicted increases in recipients' negative mood. The deleterious effects of more aggressive humor were exacerbated in recipients who were more anxiously attached. Providers who used more affiliative humor were also more empathically accurate, and providers involved with more avoidantly attached partners and who used more aggressive humor were less judgmental and more validating of their avoidant partner's behavior.